Impact of Ca2+ and Mg2+ on the Removal of F− by Magnesium Potassium Phosphate. Issue 11 (7th November 2019) - Deng, Linyu; Wang, Ying; Huang, Tinglin
Abstract: This study investigates the influence of Ca 2+ and Mg 2+ on the removal of F − by magnesium potassium phosphate (MPP) from water. The kinetic experiments reveal that the F − concentration decreased from 3.5 to 3.31 mg L −1 in a single (F − ) system and to 1.45 mg L −1 in a ternary system (F −, Ca 2+, and Mg 2+ ) after 1 min, respectively. Thus, the F − removal efficiencies are found to increase by about 53% with the co‐active effect of Ca 2+ and Mg 2+ in the solution. Moreover, Ca 2+ and Mg 2+ are almost completely removed in the F −, Ca 2+, and Mg 2+ system. According to the pseudo‐first‐order modeling, the rate constants k for F −, Ca 2+, and Mg 2+ are 0.00348, 0.0106, and 0.0159 min −1 respectively; thus, Mg 2+ > Ca 2+ > F − . In the ternary system, the removal efficiencies are 53.29–66.03% for F −, 99.99–100% for Ca 2+, and 87.21–95.19% for Mg 2+ with initial pH 5–10. The removal efficiencies of F − increases with increases in initial concentrations of F −, Ca 2+, and Mg 2+ . The removal of F − is governed by two routes: 1) adsorption by electrostatic interactions and outer sphere surface complexation; 2) co‐precipitation with Ca3 (PO4 )2, CaHPO4, Mg3 (PO4 )2, and Mg(OH)2 . Abstract : The effects of Ca 2+ and Mg 2+ on the removal of F − using MPP are evaluated: Ca 2+ and Mg 2+ could largely improve the removal of F − . This suggests that the removal of F − is governed by two routes: 1) adsorption by electrostatic interactions and outer sphere surface complexation, and 2) co‐precipitation with Ca3 (PO4 )2, CaHPO4, Mg3 (PO4 )2, and Mg(OH)2 .